Swimming anatomy - McLeod, Ian (Human Kinetics, 2010)
Swimming Anatomy includes 74 of the most effective swimming exercises, each with step-by-step descriptions and full-color anatomical illustrations highlighting the primary muscles in action and showing how each exercise is fundamentally linked to swimming performance